MEMAHAMI POLITIK TATAPAN DALAM FILM WONDER WOMAN - Larissa Asoka Tunggadhewi; Hapsari Dwiningtyas Sulityani (Interaksi Online, 2018)
Superhero genres have been Hollywood's blockbuster for ten years, but none narrates the story of a female Superhero. The release of Wonder Woman film directed by Patty Jenkins become a commercial success and received praises globally but that didn't make this movie free from the accusation that it objectified the character. This study based on the idea that director's gender could offer a difference in the portrayal of women as a subject and aim to describe her political gaze. This research refers to a critical paradigm with discourse analysis using Sara Mills' approach and used Male gaze and Auteur as the main theories. Research findings show that the personal (like political gaze) can indeed be political. The character has a maternal, sensitive, and naive trait which identified as a female attributes and have never shown in the lead character of a Superhero films before. Fragmentation like chest, buttocks, and those which portray women from foot to head did not occur. Patty Jenkins was able to add a message of female subjectivity in the film genre that is identic to the masculine audience, but she still can not escape the Male gaze. Diana's character communicates the feminine notion of peace and justice with the classic Superhero charisma. The fragmentation of a robust and sturdy female physique forms a protest against the soft, passive and commodified bodies in conventional femininity even though it still contains scopophilia. Diana's focalizations portray the subjectivity of women as feminine and heroic subjects. The schemata analysis based on the cinema's structure show director's political gaze which communicates that femininity is power and not a weakness.